Immunohistochemistry and polymerase chain reaction for detection of Mycoplasma hyopneumoniae infection in piglets - Moorkamp, L.; grosse Beilage, E.; Hewicker-Trautwein, M. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2010)
Objective: Few studies exist that concentrate on the detection of M. hyopneumoniae by PCR in piglets. Most of these studies do not permit the differentiation of latent infections from infections with typical pathomorphological lesions. The aim of the study was to characterize the occurrence of M. hyopneumoniae infections in piglets by combining and evaluating the results of macroscopical, histological, molecularbiological and immunohistochemical examinations. The evaluation of the suitability of the immunohistochemistry (IHC) as an alternative or as a supplement to other tests was a further aim. The study-design does not allow any conclusions regarding the prevalence of early M. hyo -pneumoniae-infections in piglets. Material and methods: 96 clinically affected piglets from eight pre-selected herds with an increased risk for M. hyopneumoniae infection were chosen for necropsy. Macroscopical and histological examinations of the lungs were performed. BALF and lung tissue were taken for the detection of M. hyopneumoniae by nested PCR (nPCR) and IHC. Results: 16 of 33 nPCR-positive piglets were positive for antigen by IHC while 63 nPCR-negative piglets were also negative for antigen by IHC (kappa index = 0.55). Of the 17 piglets with a nPCR-positive but IHC-negative test result, 12 originated from one herd leading to the assumption that not all field strains were detectable with the monoclonal antibody utilized. Fisher’s exact test showed a significant association (p < 0.0001) between detection of M. hyopneumoniae by nPCR in BALF or by IHC in lung tissue and the occurrence of typical pathological lesions. Conclusion: IHC with the monoclonal antibody used in this study is a suitable additional method but no alternative to the direct detection of M. hyopneumoniae by nPCR. Clinical relevance: In the case of the detection of M. hyopneumoniae in BALF by nPCR, typical pathological lesions can be expected with a higher probability than in nPCR-negative piglets.
Keywords: Diagnostic; enzootic pneumonia; monoclonal antibody; piglets